PEMBERIAN BAHAN ORGANIK PADA LAHAN MIRING KELAPA SAWIT TERHADAP ANALISIS KIMIA TANAH - Fitra Syawal Harahap; Iman Arman; Makruf Wicaksono; Whin Themas Mico; Abdul Rauf; Hilwa Walida (Agrica Ekstensia, 2019)
ABSTRACT Organic matter can improve soil chemical properties, where one of the efforts to add organic material can be done by giving compost. The research method is by taking soil samples done vertically by distinguishing the plane of the location from the specified coordinates with 2 points depth 0 cm - 30 cm and 30 cm - 60 cm. Soil samples were analyzed in the laboratory of PT. Socfindo Indonesia and research and technology laboratory, Faculty of Agriculture, University of North Sumatra. The results of the study concluded that soil organic matter was mostly contained in oil palm land that was already old to reach 2.61%, which was dominated by more than half the ideal soil composition. This is because weathering from parts of plants that occur over the years can be a source of organic material which can then be utilized optimally by plants, but the right way is needed in the management of organic material administration on land that has a sloping topography such as the use of conservation methods that can improve soil quality again.